2007
DOI: 10.1111/j.1750-3841.2007.00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Egg Yolk Protein and Egg Yolk Phosvitin Inhibit Calcium, Magnesium, and Iron Absorptions in Rats

Abstract: Egg yolk decreases the absorption of iron. The effects of egg yolk protein and egg yolk phosvitin on the absorption of calcium, magnesium, and iron were investigated by in vivo studies. Male Wistar rats were fed purified diets containing casein, soy protein, or egg yolk protein for 14 d. The apparent absorptions of calcium, magnesium, and iron in the rats fed the yolk protein-based diet were lower than those in rats fed the casein- and soy protein-based diets. The apparent phosphorus absorption and the apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 36 publications
2
30
1
1
Order By: Relevance
“…It was reported that some proteins, such as egg yolk protein 58 and casein, inhibited bioavailability of iron, which was caused by formation of 59 insoluble iron-protein complex, or presence of compete minerals (e.g. calcium in 60 casein (4)(5)(6)(7). Proteins and peptides, mainly from milk and meat, enhance iron 61 absorption were also reported (8)(9)(10).…”
mentioning
confidence: 99%
“…It was reported that some proteins, such as egg yolk protein 58 and casein, inhibited bioavailability of iron, which was caused by formation of 59 insoluble iron-protein complex, or presence of compete minerals (e.g. calcium in 60 casein (4)(5)(6)(7). Proteins and peptides, mainly from milk and meat, enhance iron 61 absorption were also reported (8)(9)(10).…”
mentioning
confidence: 99%
“…Así, el alto valor nutritivo fue el beneficio más reconocido de los AOA, aunque las de NSEB pensaban que los huevos y lácteos eran fuente de hierro, lo que es incorrecto, pues esos alimentos tienen factores que inhiben su absorción y que lo convierte en hierro de baja biodisponibilidad (26,27) ; esto indica que es indispensable resaltar como mensaje en la consejería cuáles son aliFigura 2. Barreras percibidas para el consumo de alimentos de origen animal según embarazadas de diferente nivel socioeconómico-Lima.…”
Section: Discussionunclassified
“…The native structure of phosvitin is more stable and resistant to the proteolytic cleavage by trypsin because of containing a high amount of serine and phosphoric amino acids, and chelating of Fe, which results in low in vivo bioavailability (Ishikawa et al 2007). Although it could be digested with trypsin after dephosphorisation, it is always time-consuming and difficult to separate free enzymes and products in the production of phosvitin phosphopeptides.…”
mentioning
confidence: 99%